Advances in the Control of Markov Jump Linear Systems with No Mode Observation - Vargas, Alessandro N.; Costa, Eduardo F.; do Val, João B. R. (SpringerBriefs in Control, Automation and Robotics,, 2016)
This brief broadens readers' understanding of stochastic control by highlighting recent advances in the design of optimal control for Markov jump linear systems (MJLS). It also presents an algorithm that attempts to solve this open stochastic control problem, and provides a real-time application for controlling the speed of direct current motors, illustrating the practical usefulness of MJLS. Particularly, it offers novel insights into the control of systems when the controller does not have access to the Markovian mode.